Управление персоналом - Базаров Тахир Юсупович (Академия, 2008)
Экземпляры: ф16 (20231214) / Инвентарный номер: 44156 / Цена: 295.46 / Сис.шифр: 65.050.2я7 / Авт.знак: Б 17 / ГРНТИ: 06 / ББК: 65.050.2я7